Effect of Different Gutter Slopes in Hydroponic Systems on the Growth and Yield of Red Pakcoy Plants (Brassica rapa L.) - Achmad Syamsu Ducha; Agus Sugianto; Anis Sholihah (AGRONISMA, 2022)
The slope of the gutters in the hydroponic system affects the growth and yield of red pakcoy plants. This study aims to determine the proper slope of the gutters on the growth and yield of red pakcoy plants with the hydroponic system (Nutrient Film Technique). The study used a simple randomized design with treatment in the form of differences in the slope of the gutter (P) consisting of four levels including: P1= 0%; P2= 2,5%; P3= 5%; P4= 7,5%. Each experimental unit was repeated 3 times and each treatment unit used 4 samples, so that 48 samples were obtained. The results showed that the P3 and P4 treatments showed the same and good response to the growth and yield of red pakcoy plants. At the end of the observation at 35 Hst, the plant length and number of leaves were 23.01 cm and 22.81 cm, respectively, and the number of leaves was 11.04 and 10.41, respectively. In the yield parameter, the total fresh weight of plants (41.09 grams/plant and 46.93 grams/plant respectively) and also showed the same and good response to fresh weight consumption (34.71 grams/plant and 40.70 grams/plant) at harvest. The harvest index variable is 85.59% and 87.93%, respectively.